FROM SUNRISE TO SUNSET: REFLECTIONS ABOUT EXPERIENCING THE URBAN CLIMATE THROUGHT THE LABOR ROUTINE OF THE STREET SWEEPER(S) AT PRESIDENTE PRUDENTE - SP, BRAZIL - Mendes, Lidiana de Pinho [UNESP]; Garcia Tommaselli, Jose Tadeu [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
This paper tries to understand the vulnerability relation that street sweepers undergo in their labor routines, emphasizing illnesses resulting from thermal discomfort and long expositions to the weather elements. Bibliographic survey, interviews and empirical analysis were the tools to qualify such discussion. The results had pointed out the existence of mental blocks that prevent the street sweeper(s) in express the realities of their labor routines. A scene of not-recognition of the vulnerability condition was find by individuals very close to this street sweeper(s), even by the labor laws of the country.
Keywords: Street sweeper(s); Presidente Prudente - SP; thermal insalubrity; labor environment; urban climate